Acute Kidney Injury Guidelines Are Associated With Improved Recognition and Follow-up for Neonatal Patients. (August 2020) - Vincent, Katherine; Murphy, Heidi J.; Ross, Julie R.; Twombley, Katherine E.
Abstract : Background: Studies demonstrate that neonatal acute kidney injury (AKI) is associated with increased morbidity and mortality. Acute kidney injury survivors are at risk for renal dysfunction and chronic kidney disease and require long-term follow-up. Purpose: To maximize identification of AKI and ensure referral, we created guidelines for diagnosis, evaluation, and management of AKI. Methods/Search Strategy: Retrospective cohort study of neonatal intensive care unit patients treated before guideline implementation (cohort 1; n = 175) and after (cohort 2; n = 52). Outcome measures included AKI incidence, documented diagnosis, and pediatric nephrology consultation. Statistical methods included t tests, Fisher exact tests, and Wilcoxon rank sum tests. Findings/Results: We found 68 AKI episodes in 52 patients in cohort 1 and 15 episodes in 12 patients in cohort 2. Diagnosis and documentation of AKI improved after guideline implementation (C1:24/68 [35%], C2: 12/15 [80%]; P = .003) as did pediatric nephrology consultation (C1:12/68 [18%]; C2: 12/15 [80%]; P < .001) and outpatient referral (C1: 3/47 [6%], C2:5/8 [63%]; P < .01). Implications for Practice: Neonatal AKI guideline implementation was associated with improvements in recognition, diagnosis, and inpatient and outpatient nephrology consultation. Early recognition and diagnosis along with specialist referral may improve outcomes among neonatal AKI survivors, ensuring appropriate future monitoring and long-term follow-up. Implications for Research: Future research should continue to determine the long-term implications of early diagnosis of AKI and appropriate subspecialty care with follow-up. Abstract : Supplemental Digital Content is Available in the Text.